Hydro-wind-solar Complementary Operation Rules Considering System Reliability and Extreme Failure - JING Han; CHEN Xiang; MENG Hongwen; LIU Benxi (Renmin Zhujiang)
The uncertainty of renewable energy output and the vulnerability under extreme weather conditions have become more and more prominent in the safety of power grid operation.The study proposes a long-term complementary operation rule generation method for hydro-wind-solar power that considers both the guaranteed rate of power generation and the extreme failure.Considering the joint output guarantee rate and the extreme failure of the hydro-wind-solar system,the method takes the maximum power generation as the goal.It uses the mixed-integer nonlinear program to carry out long-term sequence simulation joint operation of hydropower,wind power,and solar power.On this basis,the grey relation analysis is applied to screen the input factors.With the output of each hydropower station as that of the network,the BP neural network is adopted to generate the hydro-wind-solar complementary operation rules.Finally,the validity of the proposed model is verified through case analysis.The superiority of the proposed model is further demonstrated through the simulation analysis of scenarios related to different wind and solar installed capacities and extreme failure.